2001
DOI: 10.1007/s002130100849
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of aniracetam in aged rats and its mode of action

Abstract: These results indicate that aniracetam acts more effective when the forced swim stress-induced immobility is accompanied with brain dysfunction that occurs with aging. The antidepressant-like activity of aniracetam, which is probably due to the combined effects of 2-pyrrolidinone and N-anisoyl-GABA, may be mediated by mainly facilitating dopaminergic transmission (dopamine release and dopamine D2 receptor activation) through nicotinic acetylcholine receptor stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Furthermore, in the open field activity test, crocin did not show a significant effect on total locomotion [34-37]. The studies have been reported that acute and chronic administration of imipramine (10 mg/kg) significantly reduced the immobility time and confirmed its antidepressant effects [40,41]. In our study, imipramine (10 mg/kg) like previous reports decreased the immobility time as compared with neutral control group.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in the open field activity test, crocin did not show a significant effect on total locomotion [34-37]. The studies have been reported that acute and chronic administration of imipramine (10 mg/kg) significantly reduced the immobility time and confirmed its antidepressant effects [40,41]. In our study, imipramine (10 mg/kg) like previous reports decreased the immobility time as compared with neutral control group.…”
Section: Discussionsupporting
confidence: 75%
“…Different doses of crocin (12.5, 25, and 50 mg/kg) [28,39] were administered intraperitoneally (IP) for 21 days. Neutral and positive control groups received (IP) 1 mL/kg saline and 10 mg/kg imipramine, respectively [40,41]. Crocin and imipramine were dissolved in saline right before injections.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the TCA imipramine reduced immobility in the FST in both young/adult and aged mice. Similar findings were later reported by others Nakamura and Tanaka, 2001). Likewise, acute treatment with desipramine (IUPAC name: 3-(10,11-dihydro-5H-dibenzo[b,f]azepin-5-yl)-N-methylpropan-1-amine; trade name: Abbreviations: TCAs, tricyclic antidepressants; SSRIs, selective serotonin reuptake Inhibitors; SNRIs, serotonin-noradrenaline reuptake inhibitor; HAMD, Hamilton Rating Scale for Depression; MADRS, Montgomery-Åsberg Depression Rating Scale.…”
Section: Effects Of Antidepressants In Aged Rodentssupporting
confidence: 92%
“…Non-NMDA receptor targets such as the AMPA glutamate receptor may be critical to ketamine’s rapid onset of action (Maeng et al 2008; Mathew et al 2008 b ). Compounds with AMPA receptor-potentiating properties have shown antidepressant-like effects in rodents (Black, 2005; Knapp et al 2002; Li et al 2001; Nakamura & Tanaka, 2001) and AMPA receptor subunit knockout mice demonstrated features of major depressive disorder (Chourbaji et al 2008). …”
Section: Discussionmentioning
confidence: 99%